Oligometastatic recurrence in radically treated stage II lower thoracic ca oesophagus at two drain sites: a treatment challenge? - Sharma, Jyoti; Chandrakant, Lalit (International Surgery Journal, 2021)
Ca oesophagus is a dreaded malignancy with less than 15 % cure rate and majority of the patients presenting with advanced unresectable disease. Prognosis remains poor despite advances in combined modality treatments. Most common sites of loco-regional recurrence after surgery remains the mediastinal lymph node clearance area while other common sites are lung liver and bone. Unexpected sites of metastasis have been reported like skin, muscle, eyes etc. We report a case of 66-year-old male patient diagnosed with stage II poorly differentiated squamous cell carcinoma lower oesophagus radically treated with neoadjuvant chemotherapy, trans hiatal esophagectomy followed by adjuvant chemotherapy, who subsequently developed oligometastatic recurrences at two drain sites. Patient was treated with surgical excision followed by radiotherapy and chemotherapy.